Feasibility of estimating cost of diagnostic radiology and sonography services by using activity based costing - Afsoon Aeenparast; Faranak Farzadi; Farzaneh Maftoon; Telma Zahirian Moghadam (Payesh, 2015)
Objective (s): Due to rapid growth in health care expenditures in recent decades, finding new methods to control costs seems necessary. As such activity based costing (ABC) is one of the new costing methods that increasingly used by managers. This method will help managers to better control costs. This study aimed to investigate the possibility of using activity-based costing system in a specified range of imaging services (radiology and sonography) in centers under the contract of Iran Health Insurance Organization.Methods: This was a multi-phase study so different methods were used. First a review of the literature on the topic was carried out. Then related centers (public and private) were selected randomly. The study population was hospitals and radiology centers under the contract of Iran health insurance organization in Tehran, Iran.. Data was collected by system observation, review of documents and interview by system experts.Results: The centers were classified into 3 groups according to the financial documentation: For group A all 4 categories of financial data were accessible for implementation of ABC in systems. For group B the costs of unit and batch level were available and for group C only the costs of unit level can be estimated.Conclusion: The findings suggest that financial data documentation in different centers is the most important factor that affect the feasibility of using the activity-based costing techniques. To control costs in health care it seems that there is need to improve financial documentation both in public and private hospitals.